Experimental Study of Wool Shearing of Karakol Sheep of Different Constitutional Types - Naurizov, T.; Joldasbaeva, J. (Journal of Geography, Regional Planning and Development, 2024)
The wool of Karakol sheep has the highest weight compared to other types of wool in Uzbekistan and is one of the main sources of raw materials for the coarse wool industry. At the same time, it is much higher in quality than other coarse wool. Karakol sheep's wool was second only to Karakol hides in terms of value and value, but due to the conditions of the market economy, it fell to third place after meat products. During the transition from the sale of wool to the market economy, many farms lost money. Gradually, by the second period of reforms, woolen raw materials have their price, and the income increasing.